2021
DOI: 10.37120/ijttl.2021.17.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quizlet-Based Learning Activities on American High School Students’ Beliefs and Confidence in Learning Chinese as a Foreign Language

Abstract: Though it is not easy for Western learners to master, the Chinese language has gain its popularity in the United States in recent years. Modern digital instructional technologies can address some issues in learning difficulties of the language. This study examined the effects of Quizlet-based learning activities on the attitudes, beliefs, and confidence of urban American high school students (N = 56) in learning Chinese as a second language. Results of the mixed-design ANOVA indicated that students in the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They asserted that a combination of young age and circumstances of these classes might have a part to play in achieving this natural finding. Despite their positive result regarding the effect of gamification on students' belief in their ability to speak Chinese, Wang et al (2019) reported no significant effects on their high school students' reading, listening or vocabulary acquisition. Çakıroğlu and Güler (2021) showed that while the gamification implementation accurately increased the motivation and engagement of medium and high‐level achievers, low performers remained distant.…”
Section: Resultsmentioning
confidence: 97%
“…They asserted that a combination of young age and circumstances of these classes might have a part to play in achieving this natural finding. Despite their positive result regarding the effect of gamification on students' belief in their ability to speak Chinese, Wang et al (2019) reported no significant effects on their high school students' reading, listening or vocabulary acquisition. Çakıroğlu and Güler (2021) showed that while the gamification implementation accurately increased the motivation and engagement of medium and high‐level achievers, low performers remained distant.…”
Section: Resultsmentioning
confidence: 97%
“…The implementation of Quizlet in language education can potentially augment the learning experience and facilitate the assimilation of new linguistic concepts in a more efficient and engaging manner ( Wang et al, 2021 ). While many educators and students have claimed that Quizlet improves cognitive and emotional learning outcomes, the empirical evidence supporting this claim has been mixed.…”
Section: Literature Reviewmentioning
confidence: 99%